Social-Environmental Impacts and implications on artisanal fishing in the beneficiary communities of RESEX Acaú-Goiana (PerCursos, 2022)
Artisanal fishing in the RESEX Acaú-Goiana beneficiary communities faces several socio-environmental impacts linked to the inappropriate use of natural resources and the logic of the current economic model. Our objective was to identify these socio-environmental impacts through artisanal fishermen and fisherwomen accounts. Semi-structured interviews were carried out in six beneficiary communities: Baldo do Rio, Tejucupapo, Povoação São Lourenço, Carne de vaca, Porto de Congaçari, and Acaú. From the reports, carciniculture, oil spills, sugar cane mills, garbage, and effluent dumping were the most cited as the main causes of impacts that affect artisanal fishing activity. Therefore, the reports point to the need for urgent public policies for artisanal fishermen and their way of life and the inclusion of local ecological knowledge in the management of the RESEX.
Keywords: artisanal fishermen; traditional communities; shrimp farming; oil spill; Goiana River